Eksistensi Taman Penitipan Anak dan Manfaatnya bagi Ibu Rumah Tangga yang Bekerja (Studi Kasus di TPA Dharma Asih Kota Medan) - Supsiloani, Supsiloani Supsiloani; puspitawati, puspitawati puspitawati; hasanah, noviy (JUPIIS: Jurnal Pendidikan Ilmu-ilmu Sosial, 2015)
This research aims to understand the existence and benefit of Daycare for working wives, and factors for encouraging the housewives to board out their children. The research uses the qualitative method with the descriptive approach. Selecting informants is done by purposive sampling which is amount five persons. Data are collected by the techniques of observation, in depth interview and study of document. Analysing data is done sequentially by the steps of data reduction, displaying data, and conclusion.Â  The conclusion of the research is that Play Group since founded until today is needed, which is indicated by many of working wives board out their children in the Dharma Asih Daycare. In the beginning of founding in 1980, it only can accomodate 40 toddler, and since 2009 it increases capacity to 120 toddlers. The working wives get adventage such as feel relax in conducting their works because of not only caring of their toddlers but also be nursed and educated. The motivating factors are possibility for interacting of their children with peers, ability to socialize, independent and learning for doing routin activity.